Combining Cryogel Architecture and Macromolecular Crowding‐Enhanced Extracellular Matrix Cues to Mimic the Bone Marrow Niche. Issue 1 (4th December 2022) - Martínez‐Vidal, Laura; Magno, Valentina; Welzel, Petra B.; Friedrichs, Jens; Bornhäuser, Martin; Werner, Carsten
Abstract: Transplantation of hematopoietic stem cells (HSCs)—rare cells that can self‐renew and differentiate into cells of all hematopoietic lineages—is an important treatment option for patients with hematologic diseases. Key to the regenerative potential of HSCs is their natural in vivo microenvironment—the bone marrow niche—but in vitro engineering approaches to recapitulate the biochemical and biophysical properties of the bone marrow niche are still insufficiently explored. Herein, modular macroporous cryogels, mimicking the natural 3D architecture of trabecular bone, are seeded with human bone marrow‐derived mesenchymal stromal cells and decellularized to generate tissue‐specific extracellular matrix (ECM)‐decorated scaffolds. To recapitulate the physiological concentration of biomolecules in bone marrow, the cell culture medium is supplemented with macromolecular crowders that modulate the composition, ultrastructure, and mechanical properties of the cell‐deposited ECM. The ECM‐coated cryogel scaffolds generated under crowding conditions exhibit physicochemical properties similar to those of the endosteal niche of the bone marrow. The ECM‐functionalized cryogels presented could be used in the future for the ex vivo expansion of HSCs for transplantation and may also aid in the development of more realistic hematological disease models. Abstract : The development of a bone marrow niche model that closely mimics the natural 3D architecture of trabecular bone and the extracellular stromal compartment is reported. Macroporous cryogel scaffolds are functionalized with tissue‐specific, cell‐secreted ECM biopolymers. Macromolecular crowders enhance both ECM production and altered the microstructure of the secreted biopolymers.